Data From "A Biocodicological Analysis of the Medieval Library and Archive From Orval Abbey, Belgium". (22nd February 2022) - Bethencourt, Jorsua Herrera; Palomo, Ismael Rodríguez; Hickinbotham, Simon; Nair, Bharath; Soncin, Silvia; Dieu, Marc; Collins, Matthew; Deparis, Olivier
The dataset contains the first-ever comprehensive biocodicological analysis of medieval library books and charters using Zooarchaeological Mass Spectrometry (ZooMS). Here, we analyze 68 codices and 59 charters (1490+59 samples in total) from one single monastic institution, namely the Cistercian abbey of Orval in present-day Belgium. The data entails both peptide mass fingerprinting (using MALDI-ToF) and peptide sequencing (using LC-MS/MS) analysis of almost the entire library and all the preserved single leaf charters from the monastery. MALDI-ToF data is stored in Zenodo – a multidisciplinary open access repository while the LC-MS/MS data is deposited in ProteomeXchange Consortium via PRIDE – a publicly available repository for MS-based proteomics data. Mass spectrometric data generated from an entire monastic library and archive is of immense value to integrate with multiple case studies aiming at understanding parchment production and use in medieval Europe. Paper linked with data: Ruffini-Ronzani, N., Nieus, J.F., Soncin, S., Hickinbotham, S., Dieu, M., Bouhy, J., Charles, C., Ruzzier, C., Falmagne, T., Hermand, X., Collins, M.J. and Deparis, O 2021. A biocodicological analysis of the medieval library and archive from Orval Abbey, Belgium. Royal Society Open Science, 8 (6), p.210210.